OP0119 NOT ALL THE SAME? REACHING REMISSION REDUCES THE RISK OF CVD IN PATIENTS WITH RA, BUT PATIENTS ON BIOLOGICS MAY BE BETTER PROTECTED. (2nd June 2020) - Berg, I. J.; Lillegraven, S.; Kristianslund, E.; Kvien, T. K.; Aarrestad Provan, S.
Abstract : Background: Disease activity is a risk factor for the development of cardiovascular disease (CVD) in patients with rheumatoid arthritis (RA). Remission is the preferred treatment target in RA, and may be achieved by treatment with both conventional synthetic DMARDS (csDMARDs) and biologic DMARDS (bDMARDs). Objectives: To compare the risk of CVD in patients reaching RA disease remission vs. non-remission by 6 months. Additionally; to compare the risk of CVD in RA patients reaching remission on bDMARDs vs. csDMARDs Methods: The NOR-DMARD is a multi-centre prospective observational study that was established in 2000. Until 2012, patients who started on any DMARD were included, while only patients starting bDMARDSs were included after 2012. Disease activity and markers of inflammation (Erythrocyte Sedimentation Rate (ESR) and C-reactive protein (CRP mg/L) were measured at regular intervals. In these analyses we used data from baseline, 3-month and 6-month visits in patients with clinical RA included in the study from 2009. Patients with prior CVD were excluded from the study. Remission was assessed according to several criteria, and should be attained by the 6-month visit. NOR-DMARD data were linked to the National Death Registry and National Patient Register. The latter records all diagnoses given at any hospital admission, inpatient and outpatient, from 2009. CVD was defined as a diagnosis of myocardial infarction, chronic heart failure, cerebrovascular disease or sudden CV death in ICD10. Using cox-regression models, we compared the time until the first recorded CVD diagnosis RA disease remission vs non-remission for the first 4 years after start of therapy. The models were adjusted for age and gender. Additionally, we explored interactions between bDMARD vs. csDMARD, remission and non-remission in age and gender adjusted models. Results: Data were available for 3251 patients, mean (SD) age, 53.6 (13.5) years, number (%) females 2483 (76.4). The total patient years at risk were 5784, during which there were 65 CVD events. The HR across remission criteria are presented in table 1 . Patients in disease remission had a significantly lower HR for CVD compared to those not in remission. There was no statistically significant difference in HR for CVD between patients in remission who were treated with bDMARDs vs csDMARDs. Conclusion: Patients on bDMARDs who achieved DAS28, DAS28-CRP remission, or CRP less than 10 mg/L by the 6-month follow-up were less likely to experience a CVD, compared to patients not achieving remission. The HRs for CVD were higher for patients in remission on csDMARDS, compared to patients on bDMARDss, but the difference was not statistically significant and should be further explored. Disclosure of Interests: Inger Jorid Berg: None declared, Siri Lillegraven: None declared, Eirik kristianslund: None declared, Tore K. Kvien Grant/research support from: Received grants from Abbvie, Hospira/Pfizer, MSD and Roche (not relevant for this abstract)., Consultant of: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Paid instructor for: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Speakers bureau: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Sella Aarrestad Provan Consultant of: Novartis